Building capacity for diagnosis of Primary Ciliary Dyskinesia in South Africa: a descriptive study - Eze, Joy Nkiru (Department of Paediatrics and Child Health, 2025)
Background: Primary ciliary dyskinesia (PCD) is a rare genetic disorder characterized by abnormal cilia motility. Diagnostic capacity for PCD in sub-Saharan Africa (sSA) is limited; and incidence of PCD and genotype in sSA is unknown. Objectives: To determine the prevalence of PCD in children and adults with suspected PCD using a range of specialized diagnostic tests; and inform the development of local guidelines for PCD diagnosis. Methods: A prospective cross-sectional study in Cape Town, SA. Diagnostic tests performed included: nasal nitric oxide (nNO), nasal brushings for video microscopy of ciliary beat; transmission electron microscopy (TEM), immunofluorescence (IF) of ciliary protein antigens and genotyping. Results: Thirty-three participants (31 children; 2 adults) were enrolled July 2022 to July 2023 [median (IQR) age 5.6 years (3.8, 8.2); 16 (49%) males; 22 (66.7%) non-Caucasian]. The most frequent clinical characteristics were upper respiratory disease with or without hearing impairment (91%, n=30), chronic wet cough (73%, n=24), bronchiectasis (36%, n=12), neonatal respiratory distress (48%, n= 16), and situs inversus (36%, n=12); 7/17 (41%) participants recorded nNO <77nl/. Ciliary beat pattern and TEM were abnormal in 55% (n=18) and 6.1% (n=2) of the participants respectively; PCD was confirmed genetically in 5/24 (21%), of which two had abnormal IF. Two unrelated black Africans were homozygous for the same pathogenic variant in DNAAF3. Conclusion: Using a range of diagnostic modalities, the study has identified PCD cases who would have otherwise been missed or incorrectly diagnosed